2020
DOI: 10.1093/nar/gkaa520
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing and allosteric regulation modulate the chromatin binding of UHRF1

Abstract: Abstract UHRF1 is an important epigenetic regulator associated with apoptosis and tumour development. It is a multidomain protein that integrates readout of different histone modification states and DNA methylation with enzymatic histone ubiquitylation activity. Emerging evidence indicates that the chromatin-binding and enzymatic modules of UHRF1 do not act in isolation but interplay in a coordinated and regulated manner. Here, we compared two splicing variants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…Indeed, point mutations in either the TTD, PHD, or linker regions reduce UHRF1's association with chromatin in cells and compromise UHRF1's ability to maintain DNA methylation (Rothbart et al, 2013). This is further illustrated by a recent study that identified a splicing variant of mouse UHRF1, which has additional 9 amino acids inserted in the TTD-PHD finger linker region compared to canonical mouse and human UHRF1 (Tauber et al, 2020). As a result, the variant UHRF1 had distinct H3K9me3 binding profiles and displayed enhanced ubiquitination activity toward H3K9me3-modified nucleosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, point mutations in either the TTD, PHD, or linker regions reduce UHRF1's association with chromatin in cells and compromise UHRF1's ability to maintain DNA methylation (Rothbart et al, 2013). This is further illustrated by a recent study that identified a splicing variant of mouse UHRF1, which has additional 9 amino acids inserted in the TTD-PHD finger linker region compared to canonical mouse and human UHRF1 (Tauber et al, 2020). As a result, the variant UHRF1 had distinct H3K9me3 binding profiles and displayed enhanced ubiquitination activity toward H3K9me3-modified nucleosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Different reader domains of composite proteins or complexes can either work individually/independently or in combination (multivalent and/ or synergistic) with each other 26,39,40 . The overall binding strength is higher in multivalent, synergistic interactions compared to independent multivalent binding (reflecting only the sum of the individual domain binding strength).…”
Section: Pi5p Directs Multivalent Synergistic Interaction Of Huhrf1 With H3k9me3mentioning
confidence: 99%
“…Region I maps to the TTD surface groove (aka acidic patch or R pocket) 3,26 that shares binding interface with either Linker 4/ PBR 3,27 or with Linker 2 41 . Like Linker 4, Linker 2 is enriched in positively charged amino acids (RRK motifs, see Fig.…”
Section: Pi5p Mediates Interaction Of Huhrf1 Linker 2 and Linkermentioning
confidence: 99%
See 1 more Smart Citation
“…Also, oocytes exemplify the existence of splicing variants of DNMT1. Splicing variants of UHRF1 also exist in the mouse and modify the localization and binding behavior of UHRF1 ( 108 ), however the physiological role of these variants remains to be discovered.…”
Section: Introductionmentioning
confidence: 99%